P103 Role of biofilm production in recalcitrant tinea. (20th September 2022) - Gangar, Seema; Das, Shukla; Gourav, Vishal; Bhattacharya, S.N.; Pandhi, Deepika; Singh, N.P.
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objective: To determine the role of biofilm production in dermatophytic isolates from tinea infections of recalcitrant skin lesions of study patients. Methods: An observational study conducted in UCMS and GTB Hospital Delhi, in forty clinically diagnosed and mycologically confirmed cases of recalcitrant tinea infection of glabrous skin to analyze the role of biofilm production in dermatophytes. After taking written informed consent from the study population sample collection (skin scraping) was done. The scraping was then mounted in 10% potassium hydroxide (KOH) for direct microscopic examination followed by culture on Sabouraud Dextrose Agar (SDA) media with antibiotics (Chloramphenicol, Gentamicin, Cycloheximide). The fungal growth was then subjected to LPCB mount (Lactophenol cotton blue). The isolates were allowed to form in-vitro biofilms on polystyrene microtiter plates. Quantification of biofilm biomass was done using crystal violet staining and measuring the optical density (OD) at 570 nm and classified as non-adherent/non-producer, weak moderate, and strong biofilm producers. Results: Tinea corporis and cruris were the most common clinical types of dermatophytosis. T. mentegrophytes -complex was the most common dermatophyte isolated from the clinical specimens. Majority (86.84%) of isolates formed strong (OD >4 ODc) biofilms. Conclusion: There has been an increase in the incidents of chronic and recalcitrant dermatophytosis of skin. The predominance of T. mentegrophytes -complex as observed in our study highlights the importance of the pathogen in causation of current and chronic and recalcitrant dermatophytosis in India. High rate of in-vitro strong biofilm formation by the isolates indicates that these organisms might be forming biofilms in-vivo leading to chronicity and poor response to therapy.